From “imaginary” To “real”: a social history of the peasantry in Turkey (1945-1960)0 - Yıldırmaz, Sinan. (Thesis (Ph.D.)-Bogazici University.Atatürk Institute for Modern Turkish History, 2009., 2009)
This study investigates the socio-economic ve political conditions of the peasantry in Turkey during the 1945-1960 period through a social history perspective. In the meantime, this study has been prepared as a result of an attempt of rethinking the 1945-1960 period, at least through the peasants, who are chosen here as the main subject. With the transformation of the countryside during the 1945-1960 period the theoretical and political perspectives that previously had defined the peasants also changed. Due to that, during this study, the changing political and theoretical perspectives have been investigated in relation to the changing socio-economic conditions of the peasants. The changing political attitudes of the peasants have been presented through some case studies such as the Arslanköy Case. During this study the main characteristics of the rural migration movements have been investigated as the most visible effect of the rural transformation. The transformation of the peasantist perspective in the cultural sphere also has been investigated through the analysis of the making of the Village Literature genre during this period. In this study, the transformation of the peasantry from “imaginary” to “real” was analyzed through the discussion of the transformation of all the spheres that were related to the peasantry. In this way, not only the ideological developments, but also the developments and the transformation that occurred in relation to the peasantry per se became the focus of this study.
Keywords: Peasants -- Turkey.; Villages -- Turkey.; Sociology, Rural.